2017
DOI: 10.1210/jc.2017-01775
|View full text |Cite|
|
Sign up to set email alerts
|

High Serum TSH Level Is Associated With Progression of Papillary Thyroid Microcarcinoma During Active Surveillance

Abstract: Sustained elevation of serum TSH levels during active surveillance is associated with PTMC progression. Maintaining a low-normal TSH range with levothyroxine treatment during active surveillance of PTMC might be considered in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 30 publications
2
59
0
4
Order By: Relevance
“…9 In a recent study of 127 microPTC patients, the adjusted hazard ratio for progression was higher in patients with the highest serum TSH levels (HR 3.55; 95% CI, 1.22-10.28). 26 However, a similar earlier study found no significant association between TSH and microPTC progression. 27…”
Section: Active Surveillance Protocolsmentioning
confidence: 80%
See 1 more Smart Citation
“…9 In a recent study of 127 microPTC patients, the adjusted hazard ratio for progression was higher in patients with the highest serum TSH levels (HR 3.55; 95% CI, 1.22-10.28). 26 However, a similar earlier study found no significant association between TSH and microPTC progression. 27…”
Section: Active Surveillance Protocolsmentioning
confidence: 80%
“…The need for thyroid‐stimulating hormone (TSH) suppression in patients undergoing active surveillance is currently debated and may be worth evaluating in future studies, especially among young patients 9 . In a recent study of 127 microPTC patients, the adjusted hazard ratio for progression was higher in patients with the highest serum TSH levels (HR 3.55; 95% CI, 1.22‐10.28) 26 . However, a similar earlier study found no significant association between TSH and microPTC progression 27 …”
Section: Management Of Papillary Thyroid Microcarcinomamentioning
confidence: 99%
“…To assess patients eligible for AS and medical team characteristics, initial and follow-up evaluations require serial neck US to evaluate the size and location of the thyroid cancer and the status of the cervical LNs 5,6. However, in 2%–15% of patients initially eligible for AS, imaging studies and fine-needle aspiration cytology can underestimate tumor characteristics or extent, resulting in treatment delay and potentially compromising cure for patients with aggressive disease 713…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2%–15% of patients deemed eligible for AS, tumor characteristics or extent may be underestimated, resulting in treatment delay and potentially compromising cure for patients with aggressive disease 713. However, no definite biological or clinical parameters currently exist to distinguish low-risk indolent PTMC from potentially aggressive PTMC.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the characteristics at the time of diagnosis, patient age has been related to the risk of tumor growth, which is higher in young individuals (19)(20)(21)23). One study also associated serum TSH > 2.5 mIU/L with a higher risk of tumor growth (26). Importantly, low-risk mPTC is defined in the absence of known distant metastases, apparent extrathyroidal invasion or lymph node involvement, when the tumor is not adjacent to the trachea or recurrent laryngeal nerve, and when fine-needle aspiration (FNA) is not suggestive of an aggressive subtype.…”
Section: Papillary Thyroid Microcarcinomasmentioning
confidence: 99%